2017
DOI: 10.1093/aob/mcw272
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis inMusa acuminataduring compatible interactions withMeloidogyne incognita

Abstract: Background and Aims Endoparasitic root-knot nematodes (RKNs) (Meloidogyne spp.) cause considerable losses in banana (Musa spp.), with Meloidogyne incognita a predominant species in Cavendish sub-group bananas. This study investigates the root transcriptome in Musa acuminata genotypes 4297-06 (AA) and Cavendish Grande Naine (CAV; AAA) during early compatible interactions with M. incognita.Methods Roots were analysed by brightfield light microscopy over a 35 d period to examine nematode penetration and morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 69 publications
6
29
0
Order By: Relevance
“…MYBS3 (Ma08_25960) was found to be differentially expressed between cold-sensitive and cold-tolerant bananas [24]. Another publication described the M. acuminata R2R3-MYB gene Ma05_03690 being upregulated in the early response to the endoparasitic root-knot nematode Meloidogyne incognita in roots [28]. MusaMYB31 (Ma01_02850) was identified as a negative regulator of lignin biosynthesis and the general phenylpropanoid biosynthesis pathway [21].…”
Section: Identification and Genomic Distribution Of M Acuminata Myb mentioning
confidence: 99%
“…MYBS3 (Ma08_25960) was found to be differentially expressed between cold-sensitive and cold-tolerant bananas [24]. Another publication described the M. acuminata R2R3-MYB gene Ma05_03690 being upregulated in the early response to the endoparasitic root-knot nematode Meloidogyne incognita in roots [28]. MusaMYB31 (Ma01_02850) was identified as a negative regulator of lignin biosynthesis and the general phenylpropanoid biosynthesis pathway [21].…”
Section: Identification and Genomic Distribution Of M Acuminata Myb mentioning
confidence: 99%
“…This gene was found to be significantly downregulated at the transcript level as early as 3-dai [42]. LOX catalyses the oxygenation of fatty acids involved in the production of jasmonic acid (JA) [56], the signalling molecules that modulate HR.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic changes following M. incognita infection have been investigated in several species including Arabidopsis [7][8][9][10], tomato [11,12], soybean [13], Medicago truncatula [14], eggplant [15], banana [16] and bean [17]. These studies showed changes in expression of genes involved in several developmental and metabolic processes including stress response, signal transduction, phytohormones and cell wall formation, as well as phenylpropanoid biosynthesis.…”
Section: Introductionmentioning
confidence: 99%